Implementation of Problem Based Learning to Improve Studens’ motivation in Learning Science - Ana Rohmatul Laila (Universitas Sebelas Maret, 2022)
Learning motivation is one of the factors that plays a role in achieving success in the learning process. The low motivation of learners is a problem that teachers often encounter in educational activities. The purpose of this study is to explore the potential and effectiveness of problem-based learning in enhancing students' learning motivation in the subject of science. The results of this study indicate that the implementation of the problem-based learning model can be applied in teaching the subject of science to enhance students' learning motivation. This can be seen from the characteristics of the Science subject, which emphasizes active involvement of learners in performing process skills. The problem-based learning model provides an opportunity for students to be more active and independent in the learning process. Therefore, the problem-based learning model is worth considering as an innovative and engaging alternative for enhancing students' learning motivation in learning science.